Using a Camera Phone as a Mixed-Reality Laser Cannon. (26th March 2008) - Chehimi, Fadi; Coulton, Paul; Edwards, Reuben
Abstract : Despite the ubiquity and rich features of current mobile phones, mobile games have failed to reach even the lowest estimates of expected revenues. This is unfortunate as mobile phones offer unique possibilities for creating games aimed at attracting demographics not currently catered for by the traditional console market. As a result, there has been a growing call for greater innovation within the mobile games industry and support for games outside the current console genres. In this paper, we present the design and implementation of a novel location-based game which allows us turn a camera phone into a mixed-reality laser cannon. The game uses specially designed coloured tags, which are worn by the players, and advanced colour tracking software running on a camera phone, to create a novel first person shoot-em-up (FPS) with innovative game interactions and play.